2011
DOI: 10.1007/s11002-011-9154-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between in-store marketing and observed sales for organic versus fair trade products

Abstract: To stimulate sales of sustainable products, such as organic and fair trade products, retailers need to know whether their in-store instruments effectively enhance market shares. This study uses sales data and a multilevel modeling approach to explain the market shares of sustainable products according to shelf layout factors, price level, price promotions, and consumer demographics. It argues that the effect of these variables differs between organic versus fair trade products, as buying motives might differ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 43 publications
(73 reference statements)
4
39
2
Order By: Relevance
“…Firstly, retailers influence their role as intermediaries (Stewart and Hyysalo, 2008), through pricing (Shankar and Bolton, 2004), promotion, shelf space allocation and shelf positioning (van Nierop et al, 2011, Kök et al, 2009. Secondly, retailers are adept at representing their views of consumer needs to government (Marsden andWrigley, 1995, DEFRA, 2010).…”
Section: Retailers and Consumer Behaviour At Homementioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, retailers influence their role as intermediaries (Stewart and Hyysalo, 2008), through pricing (Shankar and Bolton, 2004), promotion, shelf space allocation and shelf positioning (van Nierop et al, 2011, Kök et al, 2009. Secondly, retailers are adept at representing their views of consumer needs to government (Marsden andWrigley, 1995, DEFRA, 2010).…”
Section: Retailers and Consumer Behaviour At Homementioning
confidence: 99%
“…It is therefore important to analyse their plans and actions for the types of goods that generate carbon emissions from the use of the products they sell. There has been research on strategies and space allocation choices in the interests of corporate responsibility, but largely focused either on Fairtrade products (Nicholls, 2002, Jones et al, 2003 or organic and Fairtrade food products (van Nierop et al, 2011, van Herpen et al, 2012, with the exception of Carrero and Valor (2012) for a broad range of ethical and environmental issues. There has also been research on the role of labelling schemes for relative energy efficiency in use, some of them devised by retailers (Heinzle andWüstenhagen, 2012, Horne, 2009).…”
Section: Retailers and Corporate Responsibility For Consumption Emissmentioning
confidence: 99%
See 1 more Smart Citation
“…Though some studies showed that higher price has little or no significant effect on the market share (Van Herpen et al, 2012), price premium has been found to be the main obstacle in the purchase (Byrne et al, 1992;Zanoli and Naspetti, 2002), and repeated purchase (Marian et al, 2014). Therefore, it is crucial to examine how loyalty programs that provide economic rewards for highly priced, value-added farm products influence the consumers' repeated purchase behavior.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Another successful in-store marketing strategy is the clustering of organic and fair trade products together in a store to make it easier for customers to find all organic food in one location. In addition, an increase in the number and types of organic products available for sale in a store can lead to greater purchases of these products by consumers (Bezawada & Pauwels, 2013;Van Herpen, Van Nierop, & Sloot, 2012).…”
Section: Introductionmentioning
confidence: 99%